Developmental defects in ectodermal appendages caused by missense mutation in edaradd gene in the nfr mangrove killifish kryptolebias marmoratus - Hussein A. Saud; Paul A. O’Neill; Brian C. Ring; Tetsuhiro Kudoh (Scientific Reports)
Abstract The mangrove killifish, Kryptolebias marmoratus, can reproduce with self-fertilisation, offering a unique and useful genetic tool for generation of genetic mutants and quick identification of mutated genes. From an ENU-mutated mangrove killifish line R228, we have isolated a novel mutant line, no-fin-ray/nfr in which homozygous mutant of adult fish fin ray development is largely reduced. Illumina RNAseq with 3 embryos each from mutants, siblings and the parental WT strain Hon9 (only 9 embryos as total) identified a mutation in the edaradd in a highly conserved C-terminal death domain. Edaradd is known as a cytoplasmic accessory protein for the Ectodysplasin A (EDA) signalling pathway. To confirm the crucial role of edaradd during fin development, CRISPR RNAs were designed to suppress the gene in another killifish species, Arabian killifish. Indeed, Arabian killifish edaradd crispants showed a potent reduction of the fin development with 100% frequency. Furthermore, EDA crispants also showed identical phenotypes to that of edaradd crispants, confirming the fin defect in the mutants/crispants is caused by the signalling pathway of the EDA in the killifish species. These data demonstrate a powerful genetic approach using isogenic self-fertilising mangrove killifish as a tool for identifying mutants and their mutations, and revealed the crucial role of edaradd for the first time in the fish fin development.